Viral opportunistic infections in Mauritian cynomolgus macaques undergoing allogeneic stem cell transplantation mirror human transplant infectious disease complications. (13th January 2020) - Wu, Helen L.; Weber, Whitney C.; Shriver‐Munsch, Christine; Swanson, Tonya; Northrup, Mina; Price, Heidi; Armantrout, Kimberly; Robertson‐LeVay, Mitchell; Reed, Jason S.; Bateman, Katherine B.; Mahyari, Eisa; Thomas, Archana; et al.
Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) and xenotransplantation are accompanied by viral reactivations and virus‐associated complications resulting from immune deficiency. Here, in a Mauritian cynomolgus macaque model of fully MHC‐matched allogeneic HSCT, we report reactivations of cynomolgus polyomavirus, lymphocryptovirus, and cytomegalovirus, macaque viruses analogous to HSCT‐associated human counterparts BK virus, Epstein‐Barr virus, and human cytomegalovirus. Viral replication in recipient macaques resulted in characteristic disease manifestations observed in HSCT patients, such as polyomavirus‐associated hemorrhagic cystitis and tubulointerstitial nephritis or lymphocryptovirus‐associated post‐transplant lymphoproliferative disorder. However, in most cases, the reconstituted immune system, alone or in combination with short‐term pharmacological intervention, exerted control over viral replication, suggesting engraftment of functional donor‐derived immunity. Indeed, the donor‐derived reconstituted immune systems of two long‐term engrafted HSCT recipient macaques responded to live attenuated yellow fever 17D vaccine (YFV 17D) indistinguishably from untransplanted controls, mounting 17D‐targeted neutralizing antibody responses and clearing YFV 17D within 14 days. Together, these data demonstrate that this macaque model of allogeneic HSCT recapitulates clinical situations of opportunistic viral infections in transplant patients and provides a pre‐clinical model to test novel prophylactic and therapeutic modalities.